Politik Hukum Tentang Tumpang Tindih Kewenangan Notaris - Hardini Febriani (Jurnal Hukum dan Sosial Politik, 2025)
The issue arises from Article 15 paragraph (2) letter f of the Notary Position Law (UUJN), which grants notaries the authority to draw up deeds related to land affairs but fails to clearly define the scope of that authority. This creates conflict with Article 2 of Government Regulation No. 37 of 1998 in conjunction with Government Regulation No. 24 of 2016, which stipulates that PPATs have the authority to draw up authentic deeds regarding certain legal acts in land affairs. This study employs a normative juridical method by reviewing statutory regulations and legal literature to analyze the issue. The results show that this overlapping authority leads to legal uncertainty and potential conflict between professional functions. In practice, although notaries are normatively granted authority in land-related matters, their implementation remains limited, as deeds drawn up by notaries cannot serve as a legal basis for land registration unless the notary is also appointed as a PPAT. Therefore, a legal reform is necessary, either through a revision of the UUJN or the establishment of implementing regulations that clarify each official’s authority. By doing so, legal certainty can be achieved, and inter-professional disputes can be minimized.